The temporal profile of postactivation potentiation is related to strength level - Seitz, L. B.; de Villarreal, E. S.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this investigation was to determine whether stronger individuals are able to express postactivation potentiation (PAP) earlier than weaker individuals during a vertical squat jump test. Eighteen junior elite rugby league players were divided into strong (relative 1 repetition maximum [1RM] back squat größer/gleich 2 × body mass) and weak (relative 1RM back squat <2.0 × body mass) groups. Each subject performed squat jumps before, 15 seconds, 3, 6, 9, and 12 minutes after a conditioning activity (CA) that contained 1 set of 3 back squats performed at 90% of 1RM. A force plate, which sampled at 1000 Hz, was used to determine the power output and height for each squat jump. Stronger individuals expressed PAP between 3 and 12 minutes post-CA, whereas their weaker counterparts displayed potentiation between 6 and 12 minutes post-CA. Moreover, the stronger group exhibited a significantly (p ? 0.05) higher PAP response than the weaker group at all post-CA squat jump tests. The stronger group displayed the greatest potentiation at 6 minutes post-CA, whereas the weaker group displayed the greatest potentiation response at 9 minutes following the CA. Based on these results, stronger individuals appear to be able to express PAP earlier after a CA than weaker individuals. Additionally, stronger individuals express significantly greater postactivation responses than weaker individuals. From a practical standpoint, strength and conditioning coaches should consider the athletes' strength levels when constructing postactivation complexes (CA + performance activity) as strength will dictate the time frame required between the conditioning and the performance activity.